Occurrence of Cabassous tatouay (Cingulata, Dasypodidae) in Rio Grande do Sul and its potential distribution in southern Brazil - Stefan V. de Oliveira; Luiz L. C. Corrêa; Felipe B. Peters; Fábio D. Mazim; Felipe M. Garcias; Janduhy P. dos Santos; Carlos B. Kasper (Iheringia: Série Zoologia, 2015)
ABSTRACT Cabossous tatouay Desmarest, 1804 is considered a rare species in southern South America, and Rio Grande do Sul State, Brazil, records of the species are scarce and inaccurate. This study reports 40 localities for C. tatouay, and provides a map of the species' potential distribution using ecological niche modeling (ENM). The ENM indicated that in this region C. tatouay is associated with open grasslands, including the areas of "Pampas" and the open fields in the highlands of the Atlantic Forest. This study contributes to the information about the greater naked-tailed armadillo in southern Brazil, and provides data key to its future conservation.